The use of Scripture in the Damascus document 1-8, 19-20 - Campbell, Jonathan G. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 1995)
3.4 Literature and Culture4 Scripture in the Historical Sections of the Damascus Document -- 4.1 The Historical Sections -- 4.2 Scripture in CD 1:1â€?2:1 -- 4.3 Scripture in CD 2:14â€?4:12a -- 4.4 Scripture in CD 5:15aâ€?6:11a -- 4.5 Scripture in the Historical Sections -- 5 Scripture in the Midrashic Sections of the Damascus Docuent -- 5.1 The Midrashic Sections -- 5.2 Scripture in CD 2:2â€?13 -- 5.3 Scripture in CD 4:12bâ€?5:15a -- 5.4 Scripture in CD 6:11bâ€?8:21 -- 5.5 Scripture in CD 19:1â€?33a -- 5.6 Scripture in CD 19:33bâ€?20:34